Mature Teratoma of The Lung : A Case Report - Priangga Adi Wiratama; Alphania Rahniayu; Vira Yasmina Ramadhani (MAGNA MEDIKA: Berkala Ilmiah Kedokteran dan Kesehatan, 2023)
Background:  Mature teratoma is a germinal cell tumor that is commonly found in ovaries and testis. Mature teratoma in the lung region is a rare case. According to the literature there are only 67 cases worldwide starting from 1939 to 2007. There were one cases in Dr. Soetomo general hospital during January 2013 – December 2017.Objective: Mature teratoma in the lung region is a rare case. Presenting in a case report would be beneficial for pathology databaseCase Presentation: A 19 years old man came to hospital with shortness of breath within 3 months ago. It was followed with hemoptysis, trichoptysis and coughing out tooth. CT Scan examination showed an irregular walled cavity with semisolid component and calcification along with a description of "air cresent sign". In thoracotomy tumor excision obtained multilobulated mass size 8.5x6,8x5,6 cm, yellowish-gray white color, and firm consistency. There were also hair and tooth components. The microscopic representation shows pieces of lung tissue with tumor growth coated with squamous epithel with a stroma containing adnexal skin glands, fatty tissue, cartilage tissue, and serous glands (asinar). Discussion: Mature teratoma of the lung is one of the rare tumors, with symptoms of chest pain, hemoptysis, and trichoptysis. Mature teratoma of the lung is generally cystic and multiloculated, but can also be solid, encapsulated. On microscopic examination, shows a picture of various components of ectoderm, mesoderm and endoderm.Conclusion: Mature teratoma of the lung is a rare tumor. Diagnosis was based from clinical findings, radiologic examination, and confirmed with histopathology and immunohistochemistry.